2017
DOI: 10.19128/turje.291015
|View full text |Cite
|
Sign up to set email alerts
|

Nature relatedness of pre-service teachers

Abstract: In this research, it was aimed to determine the nature relatedness of pre-service primary school and science teachers regarding various variables. "Nature Relatedness Scale (NRS)", developed by Nisbet, Zelenski and Murphy (2009) and adapted to Turkish and analyzed, terms of validity by Çakır, Kararslan , Şahin and Ertenpınar (2015), was used as data collection instrument. The research was carried out with 363 pre-service teachers in Kahramanmaraş Sütçü İmam University in the academic year of 2015-2016. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Adult females generally report stronger fear and disgust aroused by animals than males do. Th e increase in the diff erences in the reported levels of boys' and girls' fear and disgust is proved from primary school age (Albo et al, 2019;Fančovičová, 2012;Karakaya et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adult females generally report stronger fear and disgust aroused by animals than males do. Th e increase in the diff erences in the reported levels of boys' and girls' fear and disgust is proved from primary school age (Albo et al, 2019;Fančovičová, 2012;Karakaya et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of authors refer to the concept of alienation in the context of pre-school and primary school education and use it as a starting point for their considerations and research work (e.g. Karakaya et al, 2017;Loureiro & Dal-Farra, 2018;Mullenbach et al, 2018;Sahin & Alici, 2019;Vácha et al, 2019;Zeyger & Kägi, 2010), alienation from nature itself is poorly explored. Th e fi rst research paper found by our method that dealt with the concept was published in 2003.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations